2018
DOI: 10.1007/s00268-018-4750-3
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Intramedullary Nailing Versus Skeletal Traction for Treatment of Femoral Shaft Fractures in Malawi: A Prospective Economic Analysis

Abstract: Savings from IM nailing as compared with skeletal traction were achieved by shortened LOS. Although this study did not assess the effectiveness of either intervention, the literature suggests that traction carries a higher rate of complications than nailing. Investment in IM nailing capacity may yield substantial net savings to health systems, as well as improved clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Plating was identified as the most common treatment for the latter (metaphyseal multifragmentary tibial fractures). Consistent with other studies, intramedullary nailing is often the preferred fixation method for low and high-energy open tibial fractures because of its cost-effectiveness, improved function, and shorter length of hospitalization relative to other modalities 9,23-28 . However, the use of intramedullary nails for open tibial fractures has been associated with reoperation rates as high as 44% 29 .…”
Section: Discussionsupporting
confidence: 65%
“…Plating was identified as the most common treatment for the latter (metaphyseal multifragmentary tibial fractures). Consistent with other studies, intramedullary nailing is often the preferred fixation method for low and high-energy open tibial fractures because of its cost-effectiveness, improved function, and shorter length of hospitalization relative to other modalities 9,23-28 . However, the use of intramedullary nails for open tibial fractures has been associated with reoperation rates as high as 44% 29 .…”
Section: Discussionsupporting
confidence: 65%
“…Our results are consistent with previous studies that found that hospitals in these countries still face widespread deficiencies in trauma capacity, 39 and limited implant availability may be a key contributor. 40 However, these differences in preferred treatment could be because of lack of access to equipment and/or inadequate dissemination of knowledge, as intramedullary nailing has become an increasingly available method of fracture fixation in lowresource settings 41 and has been shown to be cost-effective 42,43 with improved early functional recovery and lower risk of malunion in LMICs. 44 Respondents reported not having sufficient experience with the procedures, not having the necessary equipment, or a combination of both, but our survey was not designed to detect whether one reason was more predominant than the other.…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review identified three key themes for interventions increasing timely access to surgical care: (1) assessment of current capacity, (2) task-shifting and education, and (3) intra-operative tools and surgical techniques. The recurrence of these three themes suggests a multi-pronged approach may be undertaken to improve timely surgical care: capacity assessments laid the framework for potential future interventions in India and Rwanda [5,6]; intraoperative tools and techniques brought certain surgical procedures closer to the patients who need them, reducing the need to transfer patients from district to regional hospitals in countries like Tanzania and Cambodia [7,14,15]; task-shifting and educational initiatives serve to directly increase surgical capacity through training in countries like Kenya [8][9][10][11][12][13]. Each of the interventions identified in this systematic review showcased quality improvement initiatives, demonstrating the importance of placing capacity building initiatives in the context of the existing work and local context.…”
Section: Discussionmentioning
confidence: 99%
“…Economic analysis presents a third method of evaluating time to surgical care [7]. In Malawi, a study demonstrated that there was no difference in time from admission to surgical intervention associated with two different femoral fracture management techniques of varying cost, the lower cost technique being intramedullary nailing (IM nailing), and the higher relative cost technique being skeletal traction.…”
Section: Assessment Of Accessibility To Surgical Carementioning
confidence: 99%
See 1 more Smart Citation